Pengembangan Pembelajaran Fiqih Berbasis Canva dalam Meningkatkan Hasil Belajar Siswa pada Kelas XI di Madrasah Aliyah Swasta Alwashliyah Prapat Janji - Wardani, Liza; Ananda, Rusydi; Rifai , Muhammad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
Fiqh learning in many madrasahs is still dominated by lecture methods with limited use of media, resulting in low student engagement and motivation. This study aims to develop and validate interactive learning media based on Canva for fiqh lessons, specifically the material on Marriage in Islam, using the 4D development model (Define, Design, Develop, Disseminate). This study is a Research and Development (R&D) project conducted at MAS Al Washliyah Prapat Janji with eleventh-grade students as the subjects. The Define stage involved needs analysis through observation, interviews, and curriculum mapping. The Design stage focused on creating interactive video content that integrates text, images, and audio. The Develop stage included expert validation of content, language, and design, as well as phased testing, while the Disseminate stage was implemented through classroom media use. Data was collected through observation, questionnaires, and pre- and post-tests, then analyzed qualitatively and quantitatively using Cronbach's Alpha for reliability and N-Gain for effectiveness. The results of the study indicate that the media have an average feasibility score of 91% (very feasible) and a practicality score of 81.5%, with an increase in post-test scores and high student engagement. This study affirms the practical application of the TPACK framework in Islamic education, while also improving motivation, conceptual understanding, long-term retention, and 21st-century skills (4C). This study contributes to the educational literature by expanding the use of Canva-based digital media in Islamic education, which has been rarely explored. Further development is recommended to emphasize increasing interactivity, teacher training in digital pedagogy, and large-scale quantitative research to strengthen the evidence of the academic impact of this medium.